(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study explores the types and functions of Reiteration Relations in Steve Schleicher’s closing argument statement, using Tanskanen’s (2006) model of analysis as a foundation. The primary objective is to identify these Reiteration Relations and examine their roles within the argument. This analysis reveals the underlying messages conveyed through the use of Reiteration Relations in court. The study conceptualizes "Reiteration Relations" as encompassing various types, each serving multiple functions. In legal discourse, they are employed as a potent technique to influence and persuade the audience.